On-surface reaction between tetracarbonitrile-functionalized molecules and copper atoms - Nardi, Elena; Chen, Long; Clair, Sylvain; Koudia, Mathieu; Giovanelli, Luca; Feng, Xinliang; Muellen, Klaus; Abel, Mathieu (Journal of Physical Chemistry C, 2014)
Self-assembly at surfaces has proven to be very efficient in creating ordered, atomically controlled organic nanostructures. On-surface synthesis has recently emerged as a promising strategy to create stable structures bound by strong and irreversible covalent bonds. Here we present on-surface reaction between pyrazino phenanthroquinoxaline-tetracarbonitrile (PPCN) molecules and copper atoms on a Au(111) substrate. The reaction is monitored in ultrahigh vacuum conditions by scanning tunneling microscopy and X-ray photoelectron spectroscopy (XPS). After a 475 K annealing, phthalocyanine cyclization occurs around a copper atom; the increase of annealing temperature to 540 and 675 K leads to the formation of 1D and 2D phthalocyanine polymers, respectively. This reaction is confirmed by the modification of the Cu 2p3/2 and C 1s XPS spectra upon annealing. (Figure Presented)
CRIS-Team Scopus Importer:2023-03-20